Optimization of Public Services in District Governments in the Archipelago - Musdalifah Haz; Sunardi; Hermanu Iriawan (Gema Kampus IISIP YAPIS Biak, 2026)
This study aims to analyze the optimization of public services at the East Numfor District Office, Biak Numfor Regency and identify the factors that affect its implementation. The research uses a qualitative descriptive approach with data collection techniques through observation, in-depth interviews, and documentation. The research informants consisted of district officials, honorary staff, village heads, and community leaders. Data analysis is carried out through data reduction, data presentation, and descriptive conclusion drawing based on five dimensions of service quality, namely reliability, responsiveness, assurance, empathy, and real evidence. The results of the study show that public services at the East Numfor District Office have been optimally pursued through the commitment of the apparatus in providing services to the community. Therefore, it is necessary to strengthen institutional capacity through the provision of adequate service facilities, improve the discipline of the apparatus, and develop a service system that is more adaptive to the characteristics of the archipelago to improve the quality of public services.